Phytoliths of bamboo affect the feeding pattern of Giant panda (Ailuropoda melanoleuca) - Tikka, Janika; Varrela, Juha; Määttä, Jorma; Salo, Jukka; Zhang, Hemin; Niemelä, Pekka; Haapakoski, Marko; Vallittu, Pekka K. (Springer Science and Business Media LLC, 2025)
Giant panda's evolutionary adaptation for using bamboo as food has been demonstrated by the morphology premolars, and by the anatomy and function of the temporomandibular joint. Pandas feed on the leaves, limbs and stem of bamboo containing phytoliths. We characterized phytoliths of two bamboo species in order to determine which parts of bamboo could contain wear-causing phytoliths and to explain panda feeding behavior to remove the cortex of the stem of bamboo before eating. Two bamboo species (Phyllostachys aureosulcata and Phyllostachys bissetii) were characterized for their inorganic content, morphological chemical and microhardness. Analysis showed that there were less inorganic minerals in the stem than in the leaves of both bamboo species. Particle size of inorganic substance was larger in the leaves and they were classified to phytoliths whereas minerals in the cortex of stem were of nanometer scale. Mean wt% of inorganic substance in leaves was 6.9% and of cortex 1.1%. Phytoliths sizes in the leaves were 30-40 µm in diameter. Amorphous silica was the major oxide. Microhardness of the outer surface of the cortex, was higher than in the subcortical layer. Panda's feeding behavior, involving the removal of stem cortex may relate to the physical properties of the cortex. Synergistic causative factor of tooth wear may exist.